Significant therapeutic effectiveness of durvalumab after chemoradiotherapy for a patient with post‐operative recurrent pulmonary pleomorphic carcinoma. Issue 6 (11th May 2021) - Shimamura, So; Saiki, Masafumi; Ide, Shuichiro; Masuda, Kazuki; Uchida, Yoshinori; Sogami, Yusuke; Kasai, Kazunari; Inoue, Tomohiro; Ishihara, Hiroshi
Abstract: Pulmonary pleomorphic carcinoma (PPC) is a poorly differentiated non‐small cell lung cancer. Because of its rarity, no standard therapy has been established for advanced disease. We herein report on a 62‐year‐old man with recurrent post‐operative PPC, for whom durvalumab after chemoradiotherapy was effective. He was referred to our hospital because of an abnormal shadow in the right upper lung on chest X‐ray. After surgical resection was performed, the imaging and histopathological findings revealed PPC (T4N0M0, stage IIIA) with elevated expression of programmed cell death‐ligand 1 (PD‐L1). A metastasis was found in the left hemithorax 22 months later, and chemoradiotherapy consisting of 60 Gy of radiation and cisplatin plus tegafur/gimeracil/oteracil potassium was administered. Durvalumab was then begun as consolidation therapy. The efficacy of the treatments has continued for longer than 10 months. This case suggests that multidisciplinary treatment with chemoradiotherapy and consolidation immunotherapy may improve the prognosis of locally advanced PPC. Abstract : Pulmonary pleomorphic carcinoma (PPC) is a poorly differentiated non‐small cell lung cancer. No standard therapy has been established for advanced disease. We herein report on a 62‐year‐old man with recurrent post‐operative PPC, for whom durvalumab after chemoradiotherapy was effective.